A large neighbourhood search to solve capacitated planar location-allocation problem - Luis, Martino; Lamsali, Hendrik; Surya Saputra, Ruswiati (2014)
This paper presents a large neighbourhood search for solving the planar location-allocation problem. This location-allocation problem entails to find the location of specified number of facilities on a plane and their customer allocations on a plane. It is generally assumed that all facilities have the same given capacity. A greedy algorithm is used to generate initial solutions and then an exchange neighborhood procedure is put forward to explore large neighborhood heuristically. The experiments are conducted to assess the performance of the proposed method using benchmark data sets taken from the facility location literature. The preliminary computational results show that the proposed methods provide competitive results when compared to the best known results from the literature. Some future research investigations on this capacitated planar location problem are also briefly highlighted.